The Phenomenology of Redemptive Violence. Issue 4 (November 2020) - Beaumont, Thomas E.
When we occupy the spaces of war memorials, we respond with certain bodily comportments that relay the "truth" of those killed by war violence. Through a phenomenological examination of embodied responses to two war memorials, the Vietnam Veterans Memorial Wall and the Tomb of the Unknown Soldier at Arlington National Cemetery, I argue that social institutions employ bodies as a means of legitimizing a violence that is seen as redemptive. More specifically, I demonstrate how the redemptive quality of certain types of violence is an assumption replicated in social practices where individuals have learned the particular bodily skills of discourses surrounding redemptive violence.